Inventare l’altro. Forme di pseudo-traduzione nella scrittura di Salvatore Di Giacomo e Luigi Capuana (TEST Ticontre. Theory Text Translation, 2014)
Being an extreme case of fictitious representation of linguistic otherness, pseudo-translation challenges the idea of a fatal and exclusive link between language and national ethos, a fundamental notion in the Nineteenth-century linguistic and literary culture. The present article compares two emblematic cases of pseudo-translation in post-Unification Italian culture: Luigi Capuana’s hoax Un poeta danese (published in 1882) and the earliest short stories published by Salvatore di Giacomo in 1878, mistakenly considered a plagiarizing translation from an uncredited German original. Their use of pseudo-translation is marked by opposite goals of parody and stylistic imitation; however, both authors challenge the fundamental assumption underlying the notion of «ethnicity of language». Pseudo-translation thus becomes a space of linguistic elaboration, complementary to the author’s direct involvement in translating major European works into Italian (such as Ibsen’s masterpiece A House of Dolls, which Capuana translated in 1891, and Edmond de Goncourt’s novel Sœur Philomèle, which Di Giacomo translated in 1892). Translation thus provides a free space for authors to experiment with new expressive solutions and challenge commonplaces about language and identity: such reflection on the limits of language and nations represent a direct contribution to the linguistic unification of Italy. Caso estremo di rappresentazione fittizia del- l’alterità linguistica, la pseudo-traduzione chiama in causa l’idea del legame unico e “fatale” fra lingua e nazione – concetto fondamentale nella cultura linguistica del XIX secolo. L’articolo mette a confronto due casi emblematici di pseudo-traduzione nella cultura meridionale post-unitaria: la beffa letteraria di Luigi Capuana Un poeta danese (1882) e le ‘tedescherie’ di Salvatore di Giacomo, gruppo di novelle pubblicate nel 1878 che molti considerarono (a torto) un plagio da ignoto autore tedesco. Questi opposti usi della pseudo-traduzione (parodico l’uno e involontario l’altro), mettono in discussione la ten- denza a considerare l’“etnicità” e l’intraducibilità di un testo come un indice del suo valore; al tempo stesso, la riflessione maturata in queste pratiche si intreccia alle traduzioni vere e proprie operate da entrambi gli autori: quella capuaniana di Casa di bambola (1891) e quella di Di Giacomo di Suor Filomena di E. de Goncourt (1892). La traduzione diventa quindi un vero e proprio laboratorio linguistico, luogo di una “strana teoria” che permette di esprimere dubbi sulle idées réçues riguardo a lingue e nazioni, senza tuttavia mettere in discussione la propria poetica autoriale. La riflessione sul rapporto tra lingue e sistemi letterari, condotta mediante il ricorso a pratiche traduttive e pseudo-traduttive, finisce così per intrecciarsi al più vasto processo di unificazione linguistica e culturale successivo all’Unità.